2009
DOI: 10.1161/atvbaha.108.181081
|View full text |Cite
|
Sign up to set email alerts
|

Fibronectin Is an Important Regulator of Flow-Induced Vascular Remodeling

Abstract: Objective Fibronectin is an important regulator of cell migration, differentiation, growth, and survival. Our data show that fibronectin also plays an important role in regulating extracellular matrix (ECM) remodeling. Fibronectin circulates in the plasma, and is also deposited into the ECM by a cell dependent process. To determine whether fibronectin affects vascular remodeling in vivo, we asked whether the fibronectin polymerization inhibitor, pUR4, inhibits intima-media thickening, and prevents excess ECM d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
164
0
2

Year Published

2011
2011
2021
2021

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 147 publications
(180 citation statements)
references
References 60 publications
(87 reference statements)
14
164
0
2
Order By: Relevance
“…We showed here that inhibition of β-catenin signaling downregulated cyclin D1 expression in CTGF transgenic lungs suggesting that cyclin D1 is one of the CTGF-β-catenin targets that may cause vascular smooth muscle cell proliferation in the neonatal lungs. Fibronectin, another β-catenin target gene, is not only a key component of vascular ECM but also an important regulator of pulmonary vascular remodeling and pulmonary arterial hypertension (36). We found that administration of ICG001 downregulated fibronectin gene expression and decreased fibronectin protein expression in peripheral pulmonary vessels in CTGF transgenic lungs.…”
Section: Discussionmentioning
confidence: 68%
“…We showed here that inhibition of β-catenin signaling downregulated cyclin D1 expression in CTGF transgenic lungs suggesting that cyclin D1 is one of the CTGF-β-catenin targets that may cause vascular smooth muscle cell proliferation in the neonatal lungs. Fibronectin, another β-catenin target gene, is not only a key component of vascular ECM but also an important regulator of pulmonary vascular remodeling and pulmonary arterial hypertension (36). We found that administration of ICG001 downregulated fibronectin gene expression and decreased fibronectin protein expression in peripheral pulmonary vessels in CTGF transgenic lungs.…”
Section: Discussionmentioning
confidence: 68%
“…FN-null MFs were cultured with 10 mg/ml fibronectin overnight in the presence or absence of pUR4, a fibronectin polymerization inhibitor. Previous studies have shown that cells elaborate a robust fibronectin matrix in the presence of the control peptide, but that pUR4 drastically reduces the deposition of ECM fibronectin (Chiang et al, 2009;Tomasini-Johansson et al, 2001). As shown in Fig.…”
Section: Fibronectin Polymerization Regulates Endocytosis Of A5b1 Intmentioning
confidence: 62%
“…FUD binds to the N-terminal assembly domain of fibronectin and prevents the fibronectinfibronectin interactions that are essential for matrix assembly ) but does not affect fibronectin expression (Chiang et al, 2009; data not shown). The III-11C peptide derived from the III-11 module of fibronectin was used as a control (Bourdoulous et al, 1998;Chiang et al, 2009). Treatment of MSCs with FUD for 24 h in a monolayer culture blocked matrix assembly (Fig.…”
Section: Condensation Depends On Fibronectin Matrix Assemblymentioning
confidence: 92%